2003
DOI: 10.1590/s0103-50532003000400010
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Prussian Blue modified carbon paste electrode (Rh-PBMCPE) for amperometric detection of hydrogen peroxide

Abstract: Filmes de azul da Prússia foram superficialmente depositados em eletrodos de pasta de carbono a partir de soluções contendo 2,0 x 10 -3 mol L -1 de K 3 [Fe(CN) 6 ], 3,0 x 10 -3 mol L -1 FeCl 3 e 1,0 x 10 -2 mol L -1 HCl, usando dois potenciais controlados. Para aumentar a estabilidade do eletrodo modificado, efetuaram-se 50 ciclos em solução contendo 1,0 x 10 -3 mol L -1 de RhCl 3 , 0,50 mol L -1 de KCl e 1,0 x 10 -2 mol L -1 de HCl no intervalo de -0,40 a + 0,60 V a 60 mVs -1 . Estes eletrodos, denominados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…1), simultaneously with a slight decrease in reversibility for the heterogeneous charge transfer process (resulting from variations of the electrochemical parameters). As was found in the case of the stabilizing effect of Ru 3+ on Co(II)-, Ni(II)-, In(III))-hexacyanoferrates, and Fe(II/III)-hexacyanorutenate [25-27, 30, 31], the stabilizing effect of Rh 3+ [28] should be due to its ability to establish an extensive cross linking between hydrate microparticles through dinuclear oxo and cyanide bridges [25,30]. Moreover, it was shown that the presence of K + ion during the potential cycling of the G/PB electrodes induces a stabilization effect, attributable to a gradual transformation of the ''insoluble'' PB into its ''soluble'' form [32][33][34].…”
Section: G/pb Modified Electrodes Preparationmentioning
confidence: 64%
See 1 more Smart Citation
“…1), simultaneously with a slight decrease in reversibility for the heterogeneous charge transfer process (resulting from variations of the electrochemical parameters). As was found in the case of the stabilizing effect of Ru 3+ on Co(II)-, Ni(II)-, In(III))-hexacyanoferrates, and Fe(II/III)-hexacyanorutenate [25-27, 30, 31], the stabilizing effect of Rh 3+ [28] should be due to its ability to establish an extensive cross linking between hydrate microparticles through dinuclear oxo and cyanide bridges [25,30]. Moreover, it was shown that the presence of K + ion during the potential cycling of the G/PB electrodes induces a stabilization effect, attributable to a gradual transformation of the ''insoluble'' PB into its ''soluble'' form [32][33][34].…”
Section: G/pb Modified Electrodes Preparationmentioning
confidence: 64%
“…Based on recently published results, which describe the beneficial effect of Ru 3+ [25][26][27] and Rh 3+ [28] on the stability of PB and its analogues (Ni(II)-, In(III)-, and Co(II)-hexacyanoferrates), the present work aims, firstly, to investigate the influence of Rh 3+ on the electrochemical behavior of PB. Secondly, PB-modified graphite electrodes (G/PB), obtained using the Ricci method [23] All solutions were prepared with purified water from a Milli-Q system (Millipore, Milford, USA) and the optimal pH was adjusted using a MV-870 Digital pH-meter (Pracitronic, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases transition metal compounds are used which may change easily their oxidation states such as hexacyanoferrates [8][9][10][11][12][13][14][15][16][17], platinum metals or their oxides [18], and manganese dioxide [6][7][8][9][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of carbonaceous materials have been investigated most often as modified electrodes for determining H 2 O 2 : graphite [6,14], glassy carbon [7,8,10,[15][16][17][18][19], carbon-paste electrodes [20,21], carbon nanotubes [22][23][24], and so forth. With these electrodes, the selectivity of the electrochemical response to hydrogen peroxide is improved by using different catalytically active modification components: transition metals and their oxides [15,21], platinum metals, dispersed on their own or mixed with other platinum metals [7,25], and with nanostructured composite films [8,26].…”
Section: Introductionmentioning
confidence: 99%